Strength-ductility synergy through microstructural and compositional heterogeneity in directed energy deposition additive manufacturing of face-centered cubic materials - Ahsan, Md R.U.; Hmeidat, Nadim S.; Islam, Saiful; Fan, Xuesong; Poplawsky, Jonathan D.; Liaw, Peter K.; Lee, Yousub; Compton, Brett G.; Jeon, Yongho; Kim, Duck Bong (Journal of Materials Research and Technology, 2024)
Directed energy deposition (DED) is an additive manufacturing (AM) process based on welding technology and offers the advantages of large build volume, high deposition rate, and ability to fabricate multi-material parts. Epitaxial continuous columnar grain growth is a characteristic microstructural feature of DED processed alloys. In this study, a bamboo-like microstructure (periodic alternation of equiaxed and columnar structure) was produced by adopting an intermittent deposition strategy in 316L stainless steel and Inconel 625. The formation of a bamboo-like alternating microstructure was confirmed through electron backscattered diffraction (EBSD) analysis. Hardness mapping showed that the columnar to equiaxed transition (CET) occurred at the region right below the fusion line. A finite element (FE) model was used to investigate the relationship between the temperature gradient (G) and the solidification rate (R). The FE model showed a low G/R ratio at the region right below the interface promoting the CET. The grain size and material-dependent deformation behaviors are analyzed using digital image correlation (DIC). The lower deformation on the fine-grain regions observed in DIC analysis is attributed to a higher strain hardening rate, which is confirmed through dislocation density analysis on a tensile-interrupted specimen. The periodically alternating grain size coupled with the microstructural changes caused by intermittent deposition strategy result in a better strength-ductility synergy in both single-material and bimetallic specimens.
Keywords: Columnar-to-equiaxed transition; Deformation mechanism; Directed energy; Directed energy deposition; Dislocations densities; Energy depositions; Finite element modelling (FEM); Grain morphologies; Grainsize; Strength-ductility synergies; Deformation mechanisms; Directed energy deposition (DED); Dislocation density; Grain morphology